Bioaccessibility of Drug Residues on Common Police Station Work Surfaces. Issue 2 (6th October 2018) - Doran, Gregory S; Howitt, Julia A
Abstract: The fraction of any surface-adsorbed contaminant available for absorption is considered the bioaccessible fraction. Applied previously to contaminants such as pesticides and heavy metals on surfaces such as soil, food and cosmetics, the term may also be used to describe the fraction of drug residue bound to work surfaces which may be mobilized via contact transfer with human skin. Police station work surfaces have been shown to commonly contain low levels of drug residues as thin films; however, no information is available on how readily these residues may be transferred to human skin during direct or glancing contact. A bioaccessibility study was undertaken in which jojoba oil and artificial sebum were used to mimic human sebum to identify how readily a mix of six licit and illicit drugs were transferred from three commonly used police station work surfaces. Transfer from surfaces was slightly greater for jojoba oil than sebum when using a direct pressure contact or a wiping motion. Generally, less than 5% of applied residues were recovered via direct contact, and up to 10% when a wiping motion was used to simulate a glancing contact. While swabbing of work surfaces with methanol provides a suitable environmental audit of drug residues present, it does not represent the bioaccessible fraction of residues available for contact transfer, and hence, absorption via skin or unintentional ingestion. The current study indicates that the ability of sebum to mobilize drug residues from thin films on work surfaces via casual contact is limited, and sebum may potentially assist in the preservation of residues on pitted work surfaces and on skin.